Analisis Sifat Mekanik Komposit Bahan Kampas Rem Dengan Penguat Serbuk Kayu Jati Dan Serbuk Kuningan - Mochamad Hisam Alamsyah; Gugun Gundara (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of this research for analyze composite material reinforced tesk wood powder and brass powder and epoxy resin matriks as brake pads material. The mix of composite brake pads divided into three kinds are Spesimen A, Spesimen B, Spesimen C, with different material composition next made to be mixing process, compacting, and sintering. This testing done with way test violence through Brinell method, test of wear rate use tool of Ogoshi high speed universal wear testing machine produce data of highest violence composite owned by Spsesimen A with score 10 HBN and highest wear rate owned by Spesimen C with score 0.0004 Kg/mm2. Composite material teak wood powder and brass powder and epoxy resin matriks have character of mechanics if composite have score of big violence so wear rate will more low and otherwise if composite have score of little violence so the wear rate will more high.